Prevalence of canine distemper in minks, foxes and raccoon dogs from 1983 to 2023 in Asia, North America, South America and Europe - Liang, Jian; Wang, Tingting; Wang, Qi; Wang, Xiaolin; Fan, Xinying; Hu, Tingting; Leng, Xue; Shi, Kun; Li, Jianming; Gong, Qinglong; Du, Rui (Frontiers in Veterinary Science, 2024)
Canine distemper (CD) is a virulent disease caused by the Canine distemper virus (CDV) in Canines and Mustelidaes with high mortality. The incidence of CD is worldwide distribution and it has caused huge economic losses to multiple industries around the world. There are many studies investigating the prevalence of CD infection, but no comprehensive analysis of CDV infection in minks, foxes and raccoon dogs worldwide has therefore been carried out. The aim of this meta is to provide a comprehensive assessment of the prevalence of CDV infection in minks, foxes and raccoon dogs through a meta-analysis of articles published from around the world. Data from 8,582 small carnivores in 12 countries were used to calculate the combined prevalence of CD. A total of 22.6%(1,937/8,582) of martens, foxes and raccoons tested positive for CD. The prevalence was higher in Asia (13.8 %, 95 % CI: 22.2-45.6), especially in South Korea (65.8 %, 95 % CI: 83.3-95.8). Our study found that the incidence of CD was also associated with geographic climate, population size, health status, and breeding patterns. CD is more commonly transmitted in minks, foxes and raccoon dogs. However ， the concentrated breeding as an economic animal has led to an increase in the prevalence rate. The difference analysis study recommended that countries develop appropriate preventive and control measures based on the prevalence in the minks, foxes, and raccoon dogs industries, and that reducing stocking density is important to reduce the incidence of CDV. In addition, CDV is more common in winter, so vaccination in winter should be strengthened with winter vaccination and expanded vaccination to reduce the incidence of CD in minks, foxes and raccoon dogs.